Шийні гривни типу «Тотенкроне» у зібранні Національного музею історії України - Осипенко, М.С.; Грицик, Ю.О. (Археологія і давня історія України, 2020)
У статті опубліковано матеріали кола балтських старожитностей: специфічні жіночі шийні гривни в декілька обертів відомі як «Тотенкроне». Проведено їхню культурно-хронологічну атрибуцію. Three years ago Ukrainian researchers from the Institute of Archaeology of the National Academy of Science have discovered and began to excavate new Balths necropolis Ostriv 1 in Kyiv region. This medieval burial ground extremely actualized in the Ukrainian scientific and public space the case on the presence of the Baltic migrants and their influence to ethnic and political processes in this region in Old Rus period.